Modeling human immunodeficiency virus-1 (HIV-1) infection in the male reproductive tract (MRT) using humanized mice - Fisher, Suhrim, author; Akkina, Ramesh, advisor; Aboellail, Tawfik, committee member; Dean, Gregg, committee member; Kendall, Lon, committee member; Weil, Michael, committee member (Colorado State University. Libraries, 2016)
Thirty-five million people are currently living with human immunodeficiency virus (HIV) globally. While 9.7 million infected people are receiving antiretroviral therapy, 2.3 million people are newly infected every year. Transmission via semen is one of the most prevalent methods of HIV-1 transmission, accounting for up to 80% of new infections every year. However, the source of infected leukocytes and the method of virus replication in semen and/or in the male reproductive tract (MRT) is not well described. It has been shown that infected germinal cells such as spermatogonia and spermatocytes as well as infected leukocytes are present in the MRT of HIV infected human patients and simian immunodeficiency virus (SIV) infected macaque models. Studies have also shown that the seminal viral strain differs from the serum viral strains in HIV infected human patients. Furthermore, HIV-1 continues to persist in the semen and in the MRT of infected male patients on highly active antiretroviral therapy (HAART) despite undetectable serum viral load. To investigate the spread and replication of HIV-1 in the MRT in human patients, development of an animal model is essential. Use of humanized mice allows researchers to study the transmission, pathogenesis and drug interactions of HIV-1 in the human immune system in vivo. The human-hematopoietic stem cell (hu-HSC) mouse model created by transplantation of HSC into Rag2−/−γc−/− mice, has shown excellent susceptibility to HIV-1 and ability to sustain high viremia for months. However, so far no studies have been conducted to demonstrate whether or not HIV-1 infiltrates and replicates in the semen or MRT of infected humanized mice. The presence of HIV-1 in the semen or MRT of infected humanized mice could play a vital role in using humanized mice for describing the pathogenesis mechanism of the virus in semen and drug development in reducing seminal HIV-1 viral load in human patients. The aim of this study is to model HIV-1 infection in the MRT using humanized mice to 1) evaluate the severity of disease using histologic scoring of MRT and morphometric analysis of the testis and epididymis in viremic and negative control mice, 2) characterize leukocytes in the testis and epididymis of viremic and negative control mice via immunohistochemistry, 3) assess the presence of HIV-1 viral RNA in the MRT of viremic mice via in situ hybridization (HIV-1 mRNA), and 4) assess seminal viral loads from vaginal plugs of viremic mice via qRT-PCR. We showed that both viremic (16/25; 64%) and negative control (9/28; 32%) mice developed histopathologic lesions in their testis and epididymis parallel to the lesions found in the testes and epididymis of chronically infected HIV-1 and AIDS patients. When broken down by two age groups, 5-7 month old and 8-12 month old, the viremic mice from both age groups showed significantly higher frequency of testicular oligospermia/azoospermia (p<0.05) compared to the age-matched negative control groups. Five to seven month old viremic mouse group showed significantly higher frequency of testicular germinal cell degeneration (p<0.05) compared to the age-matched negative control group. The histopathological lesion scores were significantly higher in both 5-7 month old and 8-12 month old viremic mouse group compared to that of age-matched negative control mouse groups (p<0.05), suggesting the lesions in viremic mice are related to HIV-1 infection. Morphometric analysis of the testicular and epididymal epithelium however, did not show any statistical differences on the levels of germinal cell degeneration between the viremic (n=8) and negative control (n=4) group. We were able to identify the presence of CD4 positive cells in viremic (4/22; 22%) and negative control (7/17; 41%) mice in the testicular and epididymal interstitium. The majority of the CD4 cells were associated with histopathologic lesions within primary reproductive organs. RNA in situ hybridization showed successful infiltration of HIV-1 infected cells in the MRT of viremic mice (9/11; 82%), most often found in penis or prepuce (6/11; 55%), and less often in seminal vesicles (4/11; 9%), testes (3/11; 27%), epididymides (1/11; 9%) and prostate glands (1/11; 9%), suggesting that HIV-1 indeed can infect and infiltrate the MRT via CD4 positive cells. Vaginal plugs failed to show detectable HIV-1 viral loads using qRT-PCR. Our study offers first glance at HIV-1 infection in the MRT of viremic humanized mice and provides further evidence that leukocytes play an important role in HIV-1 infection in the MRT.